2013
DOI: 10.1016/j.ecoleng.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Internal hydraulics of an agricultural drainage denitrification bioreactor

Abstract: Denitrification bioreactors to reduce the amount of nitrate-nitrogen in agricultural drainage are now being deployed across the U.S. Midwest. However, there are still many unknowns regarding internal hydraulicdriven processes in these engineered treatment systems. To improve this understanding, the internal flow dynamics and several environmental parameters of a denitrification bioreactor treating agricultural drainage in Northeastern Iowa, USA were investigated with two tracer tests and a network of bioreacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 31 publications
3
50
1
Order By: Relevance
“…They found that temperature was not a good predictor of removal rates, with measurements from May through August and water temperatures varying from 8.9 to 17.1°C (Christianson et al, 2013b). Our results and those of Christianson et al (2013b) suggest that bioreactors may have to be much larger to effectively remove nitrate from a typical tile line because the retention time would have to be substantially longer. On the same farm as Bioreactor 1, we monitored two constructed wetlands intercepting tile lines and found they were much more effective at reducing nitrate N loads during 2012 and 2013 (Groh et al, 2015).…”
Section: Nitrate Removal Rates In Comparison To Published Valuesmentioning
confidence: 60%
See 3 more Smart Citations
“…They found that temperature was not a good predictor of removal rates, with measurements from May through August and water temperatures varying from 8.9 to 17.1°C (Christianson et al, 2013b). Our results and those of Christianson et al (2013b) suggest that bioreactors may have to be much larger to effectively remove nitrate from a typical tile line because the retention time would have to be substantially longer. On the same farm as Bioreactor 1, we monitored two constructed wetlands intercepting tile lines and found they were much more effective at reducing nitrate N loads during 2012 and 2013 (Groh et al, 2015).…”
Section: Nitrate Removal Rates In Comparison To Published Valuesmentioning
confidence: 60%
“…Previous studies on wood chip bioreactors have found that N 2 O emissions are small, but these reports are limited (Moorman et al, 2010;Woli et al, 2010;Warneke et al, 2011a;Christianson et al, 2013b).…”
Section: Temperature and Substrate Control Woodchip Bioreactor Performentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the flow time through the filter media is of particular importance for high filter effects (e.g. Schipper and McGill 2008;Christianson et al 2012Christianson et al , 2013. A simple opportunity to extend flow times through the filter might be barriers within the filter, which allow longer times of contact.…”
Section: Discussionmentioning
confidence: 98%